Bone Loss and Muscle Atrophy in Spinal Cord Injury: Epidemiology, Fracture Prediction, and Rehabilitation Strategies - Giangregorio, Lora (American Paraplegia Society, 2006)
SUMMARY: Individuals with spinal cord injury (SCI) often experience bone loss and muscle atrophy. Muscle atrophy can result in reduced metabolic rate and increase the risk of metabolic disorders. Sublesional osteoporosis predisposes individuals with SCI to an increased risk of low-trauma fracture. Fractures in people with SCI have been reported during transfers from bed to chair, and while being turned in bed. The bone loss and muscle atrophy that occur after SCI are substantial and may be influenced by factors such as completeness of injury or time postinjury. A number of interventions, including standing, electrically stimulated cycling or resistance training, and walking exercises have been explored with the aim of reducing bone loss and/or increasing bone mass and muscle mass in individuals with SCI. Exercise with electrical stimulation appears to increase muscle mass and/or prevent atrophy, but studies investigating its effect on bone are conflicting. Several methodological limitations in exercise studies with individuals with SCI to date limit our ability to confirm the utility of exercise for improving skeletal status. The impact of standing or walking exercises on muscle and bone has not been well established. Future research should carefully consider the study design, skeletal measurement sites, and the measurement techniques used in order to facilitate sound conclusions.